Update of interferon use in acute simple bronchitis in children - A.E. Abaturov; N.M. Tokarieva (Zaslavsky O.Yu., 2018)
Background. The main etiological factors of acute simple bronchitis in children are respiratory viruses, and therefore interferon preparations can be used in the treatment of these respiratory diseases. The purpose of the work was to study the clinical and immunological efficacy of recombinant alpha 2b interferon in the treatment of acute simple bronchitis in children. Materials and methods. We have examined 49 children aged 2 to 6 years with acute simple bronchitis; 23 children received Laferobion® containing recombinant alpha 2b interferon. During the work, clinical and laboratory methods of investigation were used. The severity of the patient's condition was assessed according to the Bronchitis severity score. The laboratory study included: general blood and urine test, nasocytological, immunoassay methods. The etiological diagnosis was established using virological methods of investigation. When determining the concentration of interferon gamma, "Gamma interferon-IFA-BEST A-8752" set manufactured by Vector Best was used; lactoferrin - Нuman Lactoferrin NK 329 Edition 06-16 set manufactured by Hycult Biotech (USA), neutrophil a-defensins 1-3 - Нuman HNP NK317 Edition 08-16 reagents manufactured by Hycult Biotech (USA). Results. In all children with acute simple bronchitis, the disease began acutely and manifested itself with catarrhal and general inflammatory syndromes. According to the evaluation of acute simple bronchitis signs at the onset of the disease and in the period of convalescence using Bronchitis severity score, the administration of recombinant alpha 2b interferon promotes a faster reduction of all clinical manifestations of the disease and an increase in the lactoferrin content in the oropharyngeal fluid until the period of convalescence. Conclusions. The rectal administration of recombinant alpha 2b interferon Laferobion® is an etiopathogenetic method for the treatment of acute simple bronchitis in children